1999
DOI: 10.1177/107319119900600309
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Jungian Personality Types of Hispanic High School Students

Abstract: Measures of normal variations in personality, called psychological type, are frequently used in education (e.g., to identify learning styles) and counseling (e.g., in career counseling). However, the most frequently-used measure of types, developed by Myers and Briggs, has been criticized on various psychometric grounds. The present study investigated the psychometric properties of an alternative measure, the Personal Preferences Self-Description Questionnaire (PPSDQ), which employs normative rather than ipsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
3
2
Order By: Relevance
“…This is clearly the biggest limitation affecting our results. However, Mittag's (1999) results with Hispanic high school students were not unlike those in the present study. For example, the factor structures in both studies were very similar.…”
Section: Limitationscontrasting
confidence: 99%
See 3 more Smart Citations
“…This is clearly the biggest limitation affecting our results. However, Mittag's (1999) results with Hispanic high school students were not unlike those in the present study. For example, the factor structures in both studies were very similar.…”
Section: Limitationscontrasting
confidence: 99%
“…These coefficients were slightly better than, but generally comparable to, related PPSDQ results reported by Kier et al (1998) for a similar sample of college students from two other universities. These coefficients were higher than those reported for a sample of Hispanic high school seniors (Mittag, 1999). Such differences might be expected because the PPSDQ was administered in English, and for many of the high school students, Spanish was declared as the primary language spoken in their homes.…”
Section: Three Research Questionscontrasting
confidence: 61%
See 2 more Smart Citations
“…It has been suggested that Jungian-type differences appear in educational aptitude, application, interest, and achievement and that "type theory accounts for the different aspects of these characteristics" (Myers & McCaulley, 1985, p. 95). To overcome difficulties with the most commonly used measure of Jungian types (Vacha-Haase & Thompson, 2002), here the Personal Preferences Self-Description Questionnaire (PPSDQ) was used to measure these preferences (Arnau, Thompson, & Rosen, 1999;Kier, Melancon, & Thompson, 1998;Melancon & Thompson, 1996;Mittag, 1999).…”
Section: Research Questionsmentioning
confidence: 99%